Genomic and metabolomic insights into the biocontrol potential of Bacillus velezensis ZHR0 against sugarcane smut - Pan, Kaiyuan; Chen, Jun; Li, Huojian; Xu, Shiqiang; Wang, Jihua; Yan, Xiaoni; Zhao, Yueying; Jiang, Hongtao; Khan, Abdullah; Tahir Khan, Muhammad; Powell, Charles A.; Wen, Ronghui; et al. (Frontiers in Microbiology, 2025)
Sugarcane smut, caused by Sporisorium scitamineum, is a major disease threatening global sugarcane production. Biological control agents (BCAs) offer environmentally sustainable alternatives to chemical fungicides, with Bacillus velezensis recognized for its broad-spectrum antifungal properties. In this study, B. velezensis ZHR0 was isolated from sugarcane leaves and evaluated for its antifungal activity through in vitro dual-culture assays and in vivo greenhouse trials. Field application of a ZHR0-based biofertilizer achieved a maximum disease control efficiency of 43.86%. Whole-genome sequencing revealed a 4.04 Mb genome with a GC content of 46.48%, encoding 4,150 genes, including multiple biosynthetic gene clusters (BGCs) associated with secondary metabolite production. In vitro assays showed that ZHR0 inhibited the growth of S. scitamineum by 53.20% and reduced disease incidence in sugarcane seedlings by 45.74%. Notably, BGCs for iturin, fengycin, surfactin, and difficidin were identified, and liquid chromatography-mass spectrometry (LC-MS) confirmed the production of iturin, supporting its role in antifungal activity. These findings demonstrate the biocontrol potential of B. velezensis ZHR0 against sugarcane smut and provide integrated genomic and metabolomic evidence for its application as a sustainable biocontrol agent in sugarcane cultivation.